A function f ( x ) is such that f ( 1 ) = 2 , f ( 2 ) = 1 , and f ( x ) = f ( x − 1 ) + f ( x + 1 ) 1 for x ≥ 2 . Find
( f ( 2 0 1 4 ) f ( 2 0 1 5 ) ) ( f ( 2 0 1 2 ) f ( 2 0 1 3 ) ) . . . . . . ( f ( 2 ) f ( 3 ) ) f ( 1 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Fact:
{ f ( n ) = a f ( n + 1 ) = − a 1 ⟹ f ( n + 2 ) = − 2 a .
Proof:
Simply use the recursive formula:
f ( n + 1 ) − a 1 f ( n + 2 ) = f ( n ) + f ( n + 2 ) 1 = a + f ( n + 2 ) 1 = − 2 a □
Fact:
⎩ ⎪ ⎨ ⎪ ⎧ f ( n ) = a f ( n + 1 ) = − a 1 f ( n + 2 ) = − 2 a = b ⟹ f ( n + 3 ) = − b 1
Proof:
Simply use the recursive formula again. □ .
We also have n = 6 ⟹ { f ( n ) = a f ( n + 1 ) = − a 1 .
We can see from our proofs (and from the observation that f ( 2 ) f ( 3 ) = − 1 , f ( 4 ) f ( 5 ) = − 1 ) that f ( 2 k + 1 ) is a negative multiplicative inverse of f ( 2 k ) ∀ k ∈ N > 0 .
Thus our answer is (we also have f ( 1 ) = 2 ):
1 0 0 7 ( − 1 ) ’s ( − 1 ) ( − 1 ) ⋯ ( − 1 ) 2 = − 1
Good work man
f(x) = 1/(f(x-1)+f(x+1)); f(1)=2 ; f(2)=1. Thus, f(0) = -1/2. Thus, f(1) = 2, f(2)=1; f(3)=-1......... And thus, f(2n) = (2^(n-1))*((-1)^(n+1)). And, f(2n+1) = -(f(2n))^(-1). Thus, f(2n)f(2n+1)=-1. And, (-1)^((-1)^n) = -1.
From the first few values of f ( x ) , we note that f ( x ) f ( x + 1 ) = { 2 − 1 for x is odd. for x is even. . Let us prove by induction that the claim is true for all x ≥ 1 .
Proof: From f ( x ) = f ( x − 1 ) + f ( x + 1 ) 1 ⟹ f ( x − 1 ) f ( x ) + f ( x ) f ( x + 1 ) = 1 . For x = 1 and x = 2 , ⟹ f ( 1 ) f ( 2 ) = 2 × 1 = 2 . Then f ( 1 ) f ( 2 ) + f ( 2 ) f ( 3 ) = 1 , ⟹ 2 + f ( 2 ) f ( 3 ) = 1 , ⟹ f ( 2 ) f ( 3 ) = − 1 . Therefore, the claim is true for x = 1 and x = 2 respectively. Assuming the claim is true for x and x+1). Then, when \(x is even and x + 1 is odd, f ( x + 1 ) ( x + 2 ) = 1 − f ( x ) f ( x + 1 ) = 1 − ( − 1 ) = 2 , when x is odd and x + 1 is even, f ( x + 1 ) ( x + 2 ) = 1 − f ( x ) f ( x + 1 ) = 1 − 2 = − 1 . Therefore the claim are also true for x + 2 and x + 3 , and hence true for all x ≥ 1 .
Now we have:
X = ( f ( 2 0 1 4 ) f ( 2 0 1 5 ) ) ( f ( 2 0 1 2 ) f ( 2 0 1 3 ) ) ⋯ ( f ( 2 ) f ( 3 ) ) f ( 1 ) = ( − 1 ) ( − 1 ) ( − 1 ) ⋯ ( − 1 ) ( − 1 ) 2 = ( − 1 ) ( − 1 ) ( − 1 ) ⋯ ( − 1 ) 1 = − 1 Note that ( − 1 ) − 1 = − 1
Problem Loading...
Note Loading...
Set Loading...
f(x)f(x-1) + f(x)f(x+1) = 1.
Define g(x) = f(x)(x+1).
Then g(x) + g(x-1) = 1.
g(1) = f(1)f(2) = 2.
g(2) = 1 - g(1) = -1.
g(x+2) = 1-g(x+1) = 1-(1-g(x)) = g(x)
So these values will just repeat from here onwards. We can observe that g(x) = -1 for even x.
We are asked to find g ( 2 0 1 4 ) g ( 2 0 1 2 ) . . . g ( 2 ) 2 = − 1 − 1 . . . − 1 2 = − 1 − 1 . . . − 1 1 = − 1 − 1 − 1 − 1 = − 1 as − 1 − 1 = − 1 .